2005
DOI: 10.1002/psc.658
|View full text |Cite
|
Sign up to set email alerts
|

Conformational studies of oligomeric oxetane-based dipeptide isosteres derived fromL-rhamnose orD-xylose

Abstract: Conformational investigations have been undertaken on oligomers (dimers, tetramers, hexamers) of five closely related oxetane-based dipeptide isosteres. All the oligomers were subjected to a range of studies by NMR, FT-IR and CD spectroscopy. The oligomers derived from methyl 2,4-anhydro-5-azido-3-O-tert-butyldimethylsilyl-5-deoxy-L-rhamnonate 'monomer' all exhibited evidence of ordered conformations in chloroform and 2,2,2-trifluoroethanol (TFE) solution. 5-Acetamido and N-methylamide derivatives of the L-rha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the other hand, the trans -oxetane amino acid oligomers did not show any defined secondary structures. By contrast, trans -oxetane amino acid oligomers with a bulky 3-( tert -butyldimethylsilyl)­oxy (3-OTBS) substituent did display a defined conformation in chloroform and 2,2,2-trifluoroethanol, enforced through steric interactions without the influence of H-bonding . Cyclic tetrameric derivatives have also been prepared …”
Section: Synthesis Of Oxetane Derivatives By Intramolecular Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the trans -oxetane amino acid oligomers did not show any defined secondary structures. By contrast, trans -oxetane amino acid oligomers with a bulky 3-( tert -butyldimethylsilyl)­oxy (3-OTBS) substituent did display a defined conformation in chloroform and 2,2,2-trifluoroethanol, enforced through steric interactions without the influence of H-bonding . Cyclic tetrameric derivatives have also been prepared …”
Section: Synthesis Of Oxetane Derivatives By Intramolecular Cyclizationmentioning
confidence: 99%
“…By contrast, transoxetane amino acid oligomers with a bulky 3-(tertbutyldimethylsilyl)oxy (3-OTBS) substituent did display a defined conformation in chloroform and 2,2,2-trifluoroethanol, enforced through steric interactions without the influence of Hbonding. 188 Cyclic tetrameric derivatives have also been prepared. 189 Oxetanes have also been incorporated as side chains in βamino acids for the synthesis and conformational analysis of the foldamers they might adopt in solution.…”
Section: Synthesis Of Oxetane Derivatives By Intramolecular Cyclizationmentioning
confidence: 99%
“…The results showed that 6-deoxy-L-altronate, D-fuconate and 6-deoxy-D-gulonate oligomers are characterised by irregular non-hydrogen bonded conformations whereas L-rhamnoate and D-lyxonate oligomers have regular conformations governed by sterical interactions [50]. In contrast to the δ-2,4- trans -oxetane-SAA oligomers, the δ-2,4- cis -oxetane-L-ribonate tetramer and hexamer adopted a repeating β-turn structure [51] dictated by internal 10-membered hydrogen bonded rings.…”
Section: Reviewmentioning
confidence: 99%
“…There were two exceptions to this: the L L-rhamnoate 3 and D D-lyxonate 4, both of which exhibited an ordered structure which was not stabilised by hydrogen-bonds but was seen to be a result of steric interactions enforced by the bulky tert-butyldimethylsilyl protecting groups. 8 Herein, we report investigations into the secondary structural preferences of homo-oligomers derived from d-2,4-cis-oxetane amino acids 15 (Fig. 2), the synthesis of which was described in a preceding paper.…”
Section: Introductionmentioning
confidence: 99%